Lifestyle, entertainment and retail atmospherics of customer's preference towards a shopping mall / Nor Hashima Hashim ... [et al.] - Hashim, Nor Hashima; Lamba, Jeffery Das; Hassan, Nina Nabiha; Wan Mohd Rozihas, Wan Nursyuhada (2022)
A shopping mall is defined as an aggregation of retail and other commercial establishments owned and managed as a single property. Today, shopping malls offer services to customers in the form of convenient access to a desirable mix of retailers within a managed environment to provide a satisfying and safe shopping and leisure experience. This study aims to understand the influence of lifestyle, entertainment, and retail atmospherics on customers' preferences towards a shopping mall located in Kuala Lumpur, Malaysia. A questionnaire-based survey was conducted to collect information and a total of 250 usable questionnaires were further used for data analysis. The findings indicated that lifestyle and entertainment were significantly related to the customers' preference towards the mall. Overall, this study provides an understanding of the customers' preference for a mall and adds to the body of knowledge in understanding consumer behavior.